Ejaculate traits of ram lambs with different rectal temperatures under heat stress conditions - McCormick Palacios , Jorge Humberto; Ramírez-Valverde, Gustavo; Muñoz-García, Canuto; Maldonado Jáquez , Jorge Alonso; Hernández Aquino, Saúl; Flores Garivay, Rodrigo; Camacho Morales , Reyna Lucero; Avelar Lozano , Ernesto; González Maldonado, Juan (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: Heat stress reduces semen quality in rams. Objective: To evaluate the productive and reproductive responses of rams and ram lambs with different rectal temperatures under heat stress conditions. Methods: The animals (n = 12, Dorper × Katadhin × Pelibuey crossbreed, aged 235 to 730 days) were assigned to one of three experimental groups: ram lambs with low rectal temperature (RLLRT), ram lambs with high rectal temperature (RLHRT), and Rams. Results: Afternoon rectal temperatures were higher (p ≤ 0.05) in the RLHRT group, and there was no difference (p > 0.05) between the Rams and RLHRT groups. Ejaculate volume and sperm concentration were higher (p ≤ 0.05) in the Rams group than in the RLLRT and RLHRT groups. Mass motility and sperm concentration were lower (p ≤ 0.05) in the RLLRT group than in the RLHRT and Rams groups. Average daily weight gain did not differ (p > 0.05) between the RLLRT and RLHRT groups. Conclusion: The selection of ram lambs with low rectal temperature under heat stress conditions did not provide any benefit in terms of average daily weight gain or ejaculate traits.